Influences of post-heating treatment on crystalline phases of PVDF thin films prepared by atmospheric pressure plasma deposition. (2nd January 2019) - Jung, Eun Young; Park, Choon-Sang; Kim, Daseulbi; Kim, Soaram; Bae, Gyu Tae; Shin, Bhum Jae; Lee, Dong Ho; Chien, Sung-Il; Tae, Heung-Sik
Abstract: This paper systematically investigates the effects of the post-heating treatment on the structural characteristics of the polyvinylidene fluoride (PVDF) thin film that is deposited as the high-density thin films with nanoparticles by improving the sufficient nucleation of PVDF solution by atmospheric pressure plasma (APP) deposition system. The surface morphology of PVDF thin film was measured by using scanning electron microscopy (SEM), and structural characteristic of PVDF thin film was systematically investigated by X-ray diffraction (XRD) and Fourier transforms-infrared spectroscopy (FT-IR) with respect to different post-heating conditions in order to reduce the N, N-dimethylformamide (DMF) element and enhancing the crystalline phase of PVDF thin film. As the post-heating temperature was increased, the amount of bubble and bubble size were decreased. This means that the DMF solution is almost removed from the post-heated PVDF thin film, and the PVDF nanoparticles are clearly observed on the surface of PVDF thin film synthesized by APP deposition method. In FT-IR spectra, the peak intensity at 1669 cm −1 for -C = O by DMF solution highly decreases after post-heating treatment, and the crystalline phases of the PVDF thin film have mainly two phases (α and β phases), which indicates the peaks at 975 and 1402 cm −1 for α-phase and the peak at 1072 cm −1 for β-phase, respectively.